2022
DOI: 10.3390/s22197426
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Infants’ General Movements Using a Commercial RGB-Depth Sensor and a Deep Neural Network Tracking Processing Tool: An Exploratory Study

Abstract: Cerebral palsy, the most common childhood neuromotor disorder, is often diagnosed through visual assessment of general movements (GM) in infancy. This skill requires extensive training and is thus difficult to implement on a large scale. Automated analysis of GM performed using low-cost instrumentation in the home may be used to estimate quantitative metrics predictive of movement disorders. This study explored if infants’ GM may be successfully evaluated in a familiar environment by processing the 3D trajecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The authors concluded that ML models could be useful for healthcare services and enhance the long-term outcomes of preterm neonates. Furthermore, in a recent study, Balta et al proposed an AI-based automated monitoring of newborns' general motions, a crucial screening test for detecting neuromotor problems in children [104]. The authors created an automated model to analyze infants' overall motions, by processing videos taken with a simple camera at home.…”
Section: Neurodevelopmental Outcomementioning
confidence: 99%
“…The authors concluded that ML models could be useful for healthcare services and enhance the long-term outcomes of preterm neonates. Furthermore, in a recent study, Balta et al proposed an AI-based automated monitoring of newborns' general motions, a crucial screening test for detecting neuromotor problems in children [104]. The authors created an automated model to analyze infants' overall motions, by processing videos taken with a simple camera at home.…”
Section: Neurodevelopmental Outcomementioning
confidence: 99%
“…All infants enrolled in the pilot were nominally TD, recruited from the community, with no developmental problems of which parents were aware or communicated. However, study clinicians, specialists in pediatric neurology and physiatry, noted that the presumption of TD was difficult to confirm on video due to infants slipping into positions in the standardized infant seat that made it harder for them to choose to move one arm or the other unimpeded [ 27 ]. This observation mirrored comments from HUGS-1 parents that their babies’ movements, particularly before babies’ trunk control, was well developed, seemed awkward.…”
Section: Hugs-1 (July 2019–march 2020 Pre-lockdown Covid-19)mentioning
confidence: 99%
“…A prime example of what could be considered a failure of coaching was moving the camera during the session. This action resulted in the need to explore approaches to analysis, as stability of the camera was a pillar of the kinematic algorithm developed to analyze spontaneous movements in HUGS-1 [ 27 ]. Other actions that we did not anticipate that added complexity to analysis were bouncing the baby seat during a session and continuing to test on broken toy bars that were suspect, even though they continued to flash colored lights, play music, and vibrate.…”
Section: Hugs-2 (April 2021–november 2022: Mid-lockdown Through Early...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is parallel to the ground, separates the upper and lower parts, and is further divided into the superior and inner parts. Rotation typically occurs in this plane [ 6 , 7 , 14 , 15 , 16 ]. To explain human movement, the kinetic chain is divided into an open kinetic chain (OKC) and a closed kinetic chain (CKC).…”
Section: Introductionmentioning
confidence: 99%